2013
DOI: 10.1088/1674-1056/22/2/023401
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical simulation of the photoassociation process for NaCs

Abstract: We investigate the two-step association process of NaCs using the time-dependent wave packet method. Ground state atoms can be photoassociated to the low vibrational levels of the ground state for an NaCs molecule by the two-step association. The time-dependent Schrödinger equation of the association process is solved within a three-state model and the wave packet is propagated with the "split operator-Fourier transform" scheme and the rotating-wave approximation (RWA). The vibrational population distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In the past decade, the control of quantum degenerate gases of ultracold atoms is widely studied by exploiting collisional resonances. [1][2][3][4] Many properties of ultracold gases depend on the s-wave scatting length. [5][6][7] Magnetic-fieldinduced Feshbach resonance (MFR) is an effective tool and has been applied widely to the research of alkali atomic gases to control the interaction between atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the control of quantum degenerate gases of ultracold atoms is widely studied by exploiting collisional resonances. [1][2][3][4] Many properties of ultracold gases depend on the s-wave scatting length. [5][6][7] Magnetic-fieldinduced Feshbach resonance (MFR) is an effective tool and has been applied widely to the research of alkali atomic gases to control the interaction between atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In the investigation of light-molecule interaction, the dissociation of molecules has always been a very important topic, due to its significance in understanding both the nature of the potential energy curve (PEC) and the mechanism of the bond breaking process. [1] What is more, the progress of the photo-dissociation technique has made many new phenomena, such as multi-channel dissociation, [2] coherent control of dissociation, [3,4] photoassociation reaction, [5][6][7] etc observed and investigated. Among them, an interesting phenomenon is the double-channel dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Aymar and Dulieu [19] reported first their calculated transition dipole moments, which laid a foundation for the study of the dissociation dynamics for the NaCs molecule. In the investigation of the two-step photoassociation of some cold molecules, [7,[20][21][22] it was found that the photo-dissociation is also a crucial process. The intensive theoretical and experimental researches on alkali-metal-atom molecules [7,23] showed that because of the features of their PECs, they have great possibilities to be dissociated through the double channels when being in the electronic ground state and exposed to laser fields.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations